Integrated and Simplified Approaches to Community Management of Acute Malnutrition in Rural Kenya: AS Cluster Randomized Trial Protocol - Kimani-Murage, Elizabeth Wambui; Pythagore, Hermann; Mwaniki, Elizabeth; Daniel, Tewoldeberha; Samburu, Betty; Cuellar, Pilar Charle; Mbochi, Regina; Njiru, James; Wangare, Lucy; Karimurio, Lydia; Agutu, Olivia; Maina, Lucy Gathigi; et al. (BMC Public Health, 2019)
Background In many low income countries, the majority of acutely malnourished children are either brought to the health facility late or never at all due to reasons related to distance and associated costs. Integrated community case management (iCCM) is an integrated approach addressing disease and malnutrition through use of community health volunteers (CHVs) in children under-5 years. Evidence on the potential impact and practical experiences on integrating community-based management of acute malnutrition as part of an iCCM package is not well documented. In this study, we aim to investigate the effectiveness and cost effectiveness of integrating management of acute malnutrition into iCCM. Methods This is a two arm parallel groups, non-inferiority cluster randomized community trial (CRT) employing mixed methods approach (both qualitative and quantitative approaches). Baseline and end line data will be collected from eligible (malnourished) mother/caregiver-child dyads. Ten community units (CUs) with a cluster size of 24 study subjects will be randomized to either an intervention (5 CUs) and a control arm (5 CUs). CHV in the control arm, will only screening and refer MAM/SAM cases to the nearby health facility for treatment by healthcare professionals. In the intervention arm, however; CHVs will be trained both to screen/diagnose and also treat moderate acute malnutrition (MAM) and severe acute malnutrition (SAM) without complication. A paired-matching design where each control group will be matched with intervention group with similar characteristics will be matched to ensure balance between the two groups with respect to baseline characteristics. Qualitative data will be collected using key informant and in-depth interviews (KIIs) and focused group discussions (FGDs) to capture the views and experiences of stakeholders. Discussion Our proposed intervention is based on an innovative approach of integrating and simplifying SAM and MAM management through CHWs bring the services closer to the community. The trial has received ethical approval from the Ethics Committee of AMREF Health Africa - Ethical and Scientific Review Committee (AMREF- ESRC), Nairobi, Kenya. The results will be disseminated through workshops, policy briefs, peer-reviewed publications, and presented to local and international conferences. Trial registration PACTR201811870943127; Pre-results. 26 November 2018.
© The Author(s). 2019 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.
Keywords: Simplified; Community; Acute malnutrition; Kenya; Trial